Surgical success of patients presenting for repair of VVF - Data from fistula repair centre, Ayub Teaching Hospital, Abbottabad, Pakistan (2016-18) - Nisa Abbasi, Kosar Inayat, Azizun; Abbasi, Azizun Nisa; Inayat, Kosar (Nepal Journal of Obstetrics and Gynaecology, 2018)
Abstract: Obstetrical fistula is a devastating condition which socially impairs the life of patients in reproductive years. These females are usually socially isolated. Mostly patients don't have awareness regarding management of their problem due to poverty and ignorance. Fistula centre was estabished in Gynae department of Ayub Teaching Hospital, Abbottabad three years ago in collaboration with Pakistan National Forum on Women's Health ( PNFWH). In this presentation details of patients treated in fistula centre will be discussed.